K(+) regulates bacteroid-associated functions of Bradyrhizobium - Gober, James W. (1987)
Cowpea Bradyrhizobium 32H1 cells, when grown under 0.2% O(2), synthesize nitrogenase, as well as a methylammonium (ammonium) transport system and an electrogenic K(+)/H(+) antiporter. This effect was seen in growth medium containing 8-12 mM K(+) but not with 50 μM K(+). Addition of K(+) to cells growing under low O(2) tensions in low-K(+) medium led to various phenotypic properties associated with bacteroids, including the ability to reduce acetylene, induction of an ammonium transport carrier and the K(+)/H(+) antiporter, and increased synthesis of two heme-biosynthetic enzymes, δ-aminolevulinate synthase and δ-aminolevulinate dehydratase. K(+) addition caused the repression of glutamine synthetase and of capsular polysaccharide synthesis, functions related to the free-living state. A similar pattern of regulation was observed in Bradyrhizobium japonicum. In addition, K(+)-mediated depression in Bradyrhizobium 32H1 was inhibited by exudate of Vigna unguiculata, its host plant. We conclude that K(+) ions, in addition to low O(2) tension, are needed for the expression of several bacteroid-related functions in bradyrhizobia and thus are a major controlling influence in bacteroid development.